Analysis of Financial Statements Using the Altman Z-Score, Springate and Zmijewski Models to Predict Bankruptcy - Hamdani Hamdani*; Sari Rahmi; Asrid Juniar (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this study was to find out how the Altman Z-Score, Springate and Zmijewski models analyze bankruptcy predictions for retail companies listed on the Indonesia Stock Exchange in 2017-2021. The population of this study are Retail Companies Listed on the Indonesia Stock Exchange in 2017-2021. The research sample consisted of 24 retail companies. The data analysis model used is the Altman Z-Score, Springate and Zmijewski models. This research was conducted by taking secondary data with specified criteria from the official website of the Indonesia Stock Exchange. Based on the results of the research, it shows that the Altman Z-Score model of the sixty retail companies studied has the potential to experience bankruptcy, the Springate model of eighty-six companies that have the potential to experience bankruptcy the Zmijewski model has thirty-eight companies that have the potential to experience bankruptcy. This research is useful as reference material regarding bankruptcy prediction.